20-30 YEARS OF THE XX CENTURY UZBEK MUSIC CREATION - Nosirov Dilmurod Tursinovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article will talk about scientists who made a significant contribution to the development of Uzbek musical creativity in the 20-30s of the 20th century.